Evaluasi Ketelitian Geometri Citra Ikonos Level Geo Dearah Datar Terhadap Peta Orthofoto Skala 1:2500 - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Antar Universitas (PAU) Studi Ekonomi UGM, 2004)
Processing of IKONOS image should satisy geometric requirements, when the position reliability of depicted object want to be Unproved to a level of those produced by standard topographic map. The geometric accuracy of image depend on distributuon , number and accuracy of ground control points. Based on this consideration ,this research investigates the accuracy of the IKONOS Geo image of plan area compared to the orthophoto map of 1:2500 scale as reference. The investigation makes use of several ground control points. The evaluation is accomplished by arranging control point distribution in two different patterns. radial and a long perimeter distributions. Two sets of ground control points, consisting respectively of 15 and 25 point coordinates, are experimented in each distribution pattern. Meanwhile three mathematical models are applied in coordinate transformations i.e. linear polynomial, quadratic polynomial and cubic polynomial, so that 12transformed images are produced at the end of coordinate transformation process. The results show that radial pattern of control point distribution produces more accurate image than along perimeter distribution does. Radial distribution with 15 control points produces the best accuracy up to 0.2989 meter. All of the 12 transformed images produce root mean square error values less than 1.25 tneter, the standard accuracy of 1:2500 scale orthophoto map. It can be concluded that IKONOS image of plan area with radial distribution